2009
DOI: 10.1088/0022-3727/42/9/095001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rapid solidification on the site preference of Heusler alloy Mn2NiSb

Abstract: The site preference of Mn atoms in Heusler alloy Mn 2 NiSb can be influenced obviously by different preparing methods. Mn atoms enter the A and B sites after arc-melting and subsequent annealing, and form an Hg 2 CuTi-type of structure. However, after melt-spinning, the Mn atoms tend to occupy the (A, C) sites and form the Cu 2 MnAl-type of structure. The electronic structure calculations suggest that the Hg 2 CuTi-type of structure is lower in energy than the Cu 2 MnAl one and more stable. The lattice constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The latter has been also confirmed by experiments on Mn 2 CoGa and Mn 2 CoSn films as well as Co doped Mn 3 Ga samples, [20][21][22][23] but experiments on Mn 2 NiSb revealed that the actual arrangement of the atoms at the various sites can be influenced by the preparing method. 24 Inverse Heuslers are interesting for applications since they combine coherent growth on semiconductors with large Curie temperatures which can exceed the 1000 K as in the case of Cr 2 CoGa. 25 Slater and Pauling had shown in two pioneering papers that in the case of binary magnetic alloys when we add one valence electron in the compound this occupies spindown states only and the total spin magnetic moment decreases by about 1 µ B .…”
mentioning
confidence: 99%
“…The latter has been also confirmed by experiments on Mn 2 CoGa and Mn 2 CoSn films as well as Co doped Mn 3 Ga samples, [20][21][22][23] but experiments on Mn 2 NiSb revealed that the actual arrangement of the atoms at the various sites can be influenced by the preparing method. 24 Inverse Heuslers are interesting for applications since they combine coherent growth on semiconductors with large Curie temperatures which can exceed the 1000 K as in the case of Cr 2 CoGa. 25 Slater and Pauling had shown in two pioneering papers that in the case of binary magnetic alloys when we add one valence electron in the compound this occupies spindown states only and the total spin magnetic moment decreases by about 1 µ B .…”
mentioning
confidence: 99%
“…Understanding structural disorder in these materials is important because it can directly impact physical behaviour. 46 For half-Heusler compounds, there are five types of structural disorder that describe the distribution of atomic positions; these disorders are classified as: CaF 2 -type, BiF 3 -type, Cu 2 MnAl-type, CsCl-type, and W-type. 35 Similarly, for the full Heusler compounds, four primary types of structural disorder exist: CsCltype, BiF 3 -type, W-type, and NaTl-type.…”
Section: Structural Challengesmentioning
confidence: 99%
“…In addition, the complex magnetic structure and related effects, make the study of Heusler alloys useful for fundamental research in the field of magnetism in complex systems. Structural details like atomic site preference and magnetic coordination are important for the properties of Heusler alloys, governing magnetostructural phenomena or causing differences of several degrees in Curie temperatures [5][6].…”
Section: Introductionmentioning
confidence: 99%